Time–frequency analysis of nonstationary vibration signals for deployable structures by using the constant-Q nonstationary gabor transform. (15th June 2016) - Liu, Tao; Yan, Shaoze; Zhang, Wei
Abstract: Deployable structures have been widely used in on-orbit servicing spacecrafts, and the vibration properties of such structures have become increasingly important in the aerospace industry. The constant-Q nonstationary Gabor transform (CQ-NSGT) is introduced in this paper to accurately evaluate the variation in the frequency and amplitude of vibration signals along with time. First, an example signal is constructed on the basis of the vibration properties of deployable structures and is processed by the short-time Fourier transform, Wigner–Ville distribution, Hilbert–Huang transform, and CQ-NSGT. Results show that time and frequency resolutions are simultaneously fine only by employing CQ-NSGT. Subsequently, a zero padding operation is conducted to correct the calculation error at the end of the transform results. Finally, a set of experimental devices is constructed. The vibration signal of the experimental mode is processed by CQ-NSGT. On this basis, the experimental signal properties are discussed. This time–frequency method may be useful for formulating the dynamics for complex deployable structures. Highlights: The CQ-NSGT is modified with a zero fill operation. The modified CQ-NSGT is applied on the vibration signal of a deployable structure. The vibration properties of the deployable structure are analyzed. The limitations of STFT, Wigner-Ville distribution and HHT are discussed.